Assessing airborne transmission risks in COVID-19 hospitals by systematically monitoring SARS-CoV-2 in the air - Shanglin Li; Jiazhen Guo; Yin Gu; Yan Meng; Ming He; Shangzhi Yang; Ziruo Ge; Guanjun Wang; Yi Yang; Ronghua Jin; Lianhe Lu; Peng Liu (Microbiology Spectrum, 2023)
ABSTRACT The continuous emergence of highly infectious SARS-CoV-2 variants with the capability of immune evasion demands more effective risk assessment and management approaches for infection prevention and control. Controlling nosocomial transmission is critical in response to the COVID-19 pandemic upon the resumption of day-to-day activities. Here, we systematically analyzed the presence of airborne SARS-CoV-2 in the isolation ward and within the contaminant, emergency, and clean zones of a designated COVID-19 hospital. A total of 359 air samples collected in the clean and emergency zones tested negative for SARS-CoV-2, demonstrating the interruption of airborne transmission in a designated COVID-19 hospital by combining the closed-loop management, unidirectional airflow, and negative pressure of isolation wards. In contrast, some air samples in the corridor outside the isolation wards tested positive for SARS-CoV-2. The leakage of virus-containing air from patient rooms to adjoining areas during rounds and meal delivery sheds light on the need for intensive and widespread virus monitoring in designated COVID-19 hospitals. In conclusion, by systematically monitoring viruses in the air, the study provides a starting point for the standardization of transmission risk management in designated hospitals for the future pandemic of a newly emerged respiratory infectious disease. IMPORTANCE Risk management and control of airborne transmission in hospitals is crucial in response to a respiratory virus pandemic. However, the formulation of these infection control measures is often based on epidemiological investigations, which are an indirect way of analyzing the transmission route of viruses. This can lead to careless omissions in infection prevention and control or excessively restrictive measures that increase the burden on healthcare workers. The study provides a starting point for standardizing transmission risk management in designated hospitals by systemically monitoring viruses in the air of typical spaces in COVID-19 hospitals. The negative results of 359 air samples in the clean and emergency zones demonstrated the existing measures to interrupt airborne transmission in a designated COVID-19 hospital. Some positive cases in the corridor of the contaminant zone during rounds and meal delivery highlighted the importance of monitoring airborne viruses for interrupting nosocomial infection.